2015
DOI: 10.1080/21645515.2015.1035848
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus vaccination among adolescents in Georgia

Abstract: Human papillomavirus (HPV) vaccination coverage for adolescent females and males remains low in the United States. We conducted a 3-arm randomized controlled trial (RCT) conducted in middle and high schools in eastern Georgia from 2011-2013 to determine the effect of 2 educational interventions used to increase adolescent vaccination coverage for the 4 recommended adolescent vaccines: Tdap, MCV4, HPV and influenza. As part of this RCT, this article focuses on: 1) describing initiation and completion of HPV vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…Few studies have specifically assessed parent predictors of HPV vaccine initiation 3034 and completion 33, 34 for their adolescent girl children. Brewer and colleagues 30 found increased HPV vaccine initiation among parents when few barriers to vaccination were perceived.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Few studies have specifically assessed parent predictors of HPV vaccine initiation 3034 and completion 33, 34 for their adolescent girl children. Brewer and colleagues 30 found increased HPV vaccine initiation among parents when few barriers to vaccination were perceived.…”
Section: Introductionmentioning
confidence: 99%
“…Tsui and colleagues 32 reported that neighborhood sociodemographic factors (e.g., the percentage of census tract residents living below poverty level, the percentage of unemployed census tract residents older than age 16, the percentage of census tract residents belonging to a minority race/ethnicity, and the percentage of census tract residents without access to a private vehicle) were not significantly associated with HPV vaccine initiation after controlling for individual-level factors (e.g., the daughter’s age, insurance type, usual source of care; and the mother’s race/ethnicity, age and level of HPV awareness). According to Underwood and colleagues 33 , parents with more positive attitudes about the vaccine and with a female child were more likely to initiate and complete the series. The age of the female child and the type of insurance were also factors: having a high school age child and private insurance were associated with completing the series compared to having a middle school child and Medicaid.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Other research has shown that parents' beliefs about the general benefits of vaccines and perceived benefits of HPV vaccine were associated with initiation of HPV vaccine for their sons, 7 and that positive attitudes toward HPV vaccine among parents were the strongest predictor of HPV vaccine initiation and completion. 8 Given the importance of a provider recommendation and awareness of HPV vaccine for males, one objective of this study was to explore in more depth parents' experiences with discussing HPV vaccine with physicians. In addition, we sought to explore attitudes related to HPV vaccination among parents with adolescent sons, with a focus on comparing the perspective of parents who do not intend to initiate HPV vaccine to that of parents who are likely to initiate or continue HPV vaccination.…”
Section: Introductionmentioning
confidence: 99%